A refined protocol for the characterization of occupational exposure to organic dust in dairies - Viegas, Carla (2018)
Dairy industry workers are engaged in activities including feeding and milking of cows and cleaning up manure on a daily basis, being exposed to organic dust known to cause respiratory diseases. This study describes an updated protocol for the assessment of occupational exposure to organic dust, to unveil an accurate scenario regarding occupational risks for workers’ health. The particle size distribution was characterized regarding mass concentration in five different size ranges (PM0.5, PM1, PM2.5, PM5, PM10). Particles counts were also assessed in six different size ranges. Bioburden was assessed by air, surfaces and feed samples. Smaller size range particles exhibited the highest counts (0.3µm) in all the locations. Final product room showed the highest values for particles counts and mass. Regarding total and gram-negative bacteria, the limit wasn´t exceeded although the values were higher than outdoor for almost all samples. The limit values suggested for fungal load were surpassed in 87.5% (7 out of 8) of samples. Among Aspergillus genera, section Fumigati was the most prevalent (48.5%) on malt extract agar (MEA) and Circumdati the most identified (44.4%) on dichloran glycerol (DG18). The results document a broader characterization of occupational exposure to organic dust on dairies, being useful for policies and stakeholders to act to improve workers’ safety. Additionally, actions taken to reduce workers exposure will contribute to reducing the risk of food contamination. The methods of sampling and analysis employed should be adopted as a protocol to be followed in future exposure assessments in this occupational environment.